IMPLEMENTASI PELAKSANAAN STANDAR PELAYANAN MINIMAL PENDIDIKAN DI SEKOLAH DASAR - Nurlatifah Hidayati; R. Gunawan Sudarmanto; Irawan Suntoro (9 772338317006)
This study used a qualitative approach with case study design. Data collection techniques used in this study are interviews, documentation and observation. The results of the study are as follows: (1) The SPM in Primary School has been running based on the regulations set by the Indonesian which on the average meets the criteria for determining the appropriate SPM stated in the Minister of Education’s Regulation No. 15 of 2010, (2) The evaluation of SPM’s implementation at Primary School has been involving all stakeholders, (3) The obstacles encountered in the implementation of SPM in is the less active community participation and the lack of communication between parents and the school, (4) the support community participation in the implementation of SPM (Minimum Service Standard of Education) in Primary School is less maximum, while the principal support in the form of moral and material supports are maximum.Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, observasi dan dokumentasi. Hasil dari penelitian ini adalah sebagai berikut: (1) SPM di Sekolah Dasar telah berjalan berdasarkan peraturan yang ditetapkan oleh Indonesia yang rata-rata memenuhi kriteria untuk menentukan SPM sesuai tercantum dalam Peraturan Menteri Pendidikan No 15 tahun 2010, (2) evaluasi pelaksanaan SPM di sekolah Dasar telah melibatkan seluruh pemangku kepentingan, (3) kendala yang dihadapi dalam pelaksanaan SPM di adalah partisipasi masyarakat kurang aktif dan kurangnya komunikasi antara orang tua dan sekolah, (4) partisipasi masyarakat dukungan dalam pelaksanaan SPM (Standar Pelayanan Minimal Pendidikan) di Sekolah Dasar kurang maksimal, sementara dukungan utama dalam bentuk dukungan moral dan material maksimum.Kata kunci: implementasi standar pelayanan minimal pendidikan, keterlibatan pemangku kepentingan